Character building : membangun karakter menjadi pemimpin / Yudha Kurniawan, Tri Puji Hindarsih ; penyunting, Irin Hidayat, Yusuf Maulana - YUDHA KURNIAWAN; Tri Puji Hindarsih; Irin Hidayat; Yusuf Maulana (Pro-U Media, 2013)
306 hlm. : ilus. ; 24 cm.